Pengelolaan Bansos oleh Dinas Sosial Kota Serang (Studi Kasus Kelurahan Cipocok Kecamatan Cipocok) - Indi Juniartri Cahya Ningrum; Fara Padila; Vira Putri Damayanti; Sakti Dwiantoro Prasya; Muhamad Rihal Ramadhan; Reza Damayanti (INDO PUBLISHING, 2026)
This study aims to analyze the management of social assistance by the Serang City Social Affairs Office, with a case study focus on Cipocok Village, Cipocok Subdistrict. Social assistance programs are a crucial tool in poverty alleviation, but their implementation often faces challenges regarding data accuracy and distribution effectiveness. Using a qualitative research method with a case study approach, data were collected through in-depth interviews, observations, and public information documentation. The results indicate that the social assistance management process in Cipocok Village has followed applicable regulations, from data collection through to distribution. Nevertheless, several major obstacles were identified, such as inclusion and exclusion errors stemming from inaccuracies in the Integrated Social Welfare Data (DTKS). These obstacles are exacerbated by delays in data updates at the grassroots level and a lack of transparency in the verification and validation processes in the field. Consequently, the distribution of social assistance has not been fully targeted or equitable. This study recommends the need to strengthen a community-based data update system on a regular basis, improve coordination between the Social Affairs Office and village officials, and optimize participatory oversight to minimize misallocation and ensure transparency in the management of social assistance in the future. Theoretically, the results of this study contribute This study recommends the need to strengthen the community-based data updating system on a regular basis, improve coordination between the Social Affairs Office and village officials, and optimize participatory oversight to minimize misallocation and ensure transparency in the management of social assistance in the future. Theoretically, the results of this study provide a scientific contribution to the study of public governance, particularly in the reform of social assistance distribution administration. Practically, this study can serve as a strategic reference for the Serang City Government in formulating poverty alleviation policies that are more adaptive, accountable, and based on real data.